Sediment fluxes and biotic C cycling from stable isotope tracer incubation experiments under climate change projections in the Cabo Verde Basin, NE Atlantic - Danielle de Jonge; Daniela Y Gaurisas; Angelo Fraga Bernardino; Andrew K Sweetman (PANGAEA, 2025)
An experimental approach was developed to assess the individual and combined effects of two climate change stressors (temperature and POC quality) on soft sediments in the bathyal continental margin of the Cabo Verde Basin (CVB, Equatorial Atlantic). The study used stable isotope tracer incubation experiments with 13C and 15N labelled diatoms Phaeodactylum tricornutum, to simulate climate change projections for the next century. A balanced experimental design was employed to examine the impacts of increased temperature (+2 °C), reduced POC quality (dialysed labile fraction), or both, compared to a control treatment. The experiments were carried out onboard the research vessel Sarmiento de Gamboa during the iMirabilis2 campaign in August 2021 (Orejas et al., 2022). A total of 19 sediment samples were collected by four multi-corer (MUC) deployments. From each MUC deployment, four cores with clear overlying water were randomly selected and assigned among the four different treatments (total n= 4 for each of 4 treatments), and the remaining three cores were used as background for natural stable isotopes. The upper 15-18 cm of sediment from each core was extruded to an incubation core (inner diameter 10 cm) closed airtight at the bottom. The incubation cores were placed in buckets with filtered seawater at the experimental temperature. After an equilibration period of 147 to 173 hours, the stable isotope experiment began with the injection of 12.5 mg of fresh or partially degraded diatoms into each core, representing approximately 10% of the average annual POC flux for the region (Sweetman et al., 2017). The experiment lasted 48 hours after the algae injection, with the cores maintained under constant aeration. During the incubation, Sediment Community Oxygen Consumption (SCOC) rates and DI13C production rates were measured twice (at T10 and at T45). At the experiment extquotesingles conclusion, sediment samples were stored at -80°C for Phospho Lipid derived Fatty Acid (PLFA) analysis or fixed in 10% borax-buffered formalin seawater for macrofauna analysis (Gaurisas et al. 2024). Phospho Lipid derived Fatty Acid (PLFA) extraction according to Shahbaz et al. (2020) followed by Gas Chromatography Isotope Ratio Mass Spectrometry (GC-IRMS) according to Thornton et al. (2011), utilising bacterial biomarker C15:0i and related biomarker-specific fraction (7.4%) from Rajendran et al. (1993). Followed by adjustment for sediment Dry Bulk Density (DBD = 2.50 g cm-3) and sediment porosity (= 0.61) according to Thiede et al. (1982); followed by adjustment for bacterial-cell specific PLFA concentration (= 0.056 g C PLFA g-1 C) according to Brinch-Iversen & King (1990).